Odpowiedź:
a) ( 3 i 1/2 +1 i 1/2) *3/5= 5*3/5 ( skracamy 5 i 5 przez 5)= 3
b) ( 2 i 2/3 - 4/5 ) *1 i 3/7= ( 2 i 10/15- 12/15)* 10/3= ( 1 i 25/15- 12/15)*10/3=
=1 i 13/15*10/3= 28/15*10/3 ( skracamy 15 i 10 przez 5)= 28/3 *2/3=
= 56/9 = 6 i 2/9
c) ( 15 i 2/3 -7 i 1/2) : 1 i 1/2= ( 15 i 4/6- 7 i 3/6 ): 3/2=8 i 1/6 *2/3=
= 49/6 *2/3( skracamy 6 i 2 przez 2)= 49/3 *1/3= 49/9= 5 i 4/9
e) 4 i 1/2 *1 i 1/3 - 2 i 2/5 *5/7= 9/2 *4/3 - 12/5 *5/7( skracamy 9 i 3 przez
3, oraz 4 i 2 przez 2, oraz 5 i 5 przez 5)= 3*2 - 12*1/7=
= 6- 12/7= 5 i 7/7- 1 i 5/7= 4 i 2/7
Szczegółowe wyjaśnienie: